Hypertrophic cardiomyopathy mutations increase myofilament Ca2+ buffering, alter intracellular Ca2+ handling, and stimulate Ca2+-dependent signaling - Robinson, P; Liu, X; Sparrow, A; Patel, S; Zhang, Y; Casadei, B; Watkins, H; Redwood, C (American Society for Biochemistry and Molecular Biology, 2018)
Mutations in thin filament regulatory proteins that cause hypertrophic cardiomyopathy (HCM) increase myofilament Ca2+ sensitivity. Mouse models exhibit increased Ca2+ buffering and arrhythmias, and we hypothesized that these changes are primary effects of the mutations (independent of compensatory changes) and that increased Ca2+ buffering and altered Ca2+ handling contribute to HCM pathogenesis via activation of Ca2+-dependent signaling. Here, we determined the primary effects of HCM mutations on intracellular Ca2+ handling and Ca2+-dependent signaling in a model system possessing Ca2+-handling mechanisms and contractile protein isoforms closely mirroring the human environment in the absence of potentially confounding remodeling. Using adenovirus, we expressed HCM-causing variants of human troponin-T, troponin-I, and α-tropomyosin (R92Q, R145G, and D175N, respectively) in isolated guinea pig left ventricular cardiomyocytes. After 48 h, each variant had localized to the I-band and comprised ∼50% of the total protein. HCM mutations significantly lowered the Kd of Ca2+ binding, resulting in higher Ca2+ buffering of mutant cardiomyocytes. We observed increased diastolic [Ca2+] and slowed Ca2+ reuptake, coupled with a significant decrease in basal sarcomere length and slowed relaxation. HCM mutant cells had higher sodium/calcium exchanger activity, sarcoplasmic reticulum Ca2+ load, and sarcoplasmic/endoplasmic reticulum calcium ATPase 2 (SERCA2) activity driven by Ca2+/calmodulin-dependent protein kinase II (CaMKII) phosphorylation of phospholamban. The ryanodine receptor (RyR) leak/load relationship was also increased, driven by CaMKII-mediated RyR phosphorylation. Altered Ca2+ homeostasis also increased signaling via both calcineurin/NFAT and extracellular signal–regulated kinase pathways. Altered myofilament Ca2+ buffering is the primary initiator of signaling cascades, indicating that directly targeting myofilament Ca2+ sensitivity provides an attractive therapeutic approach in HCM.